2016
DOI: 10.1210/jc.2015-3906
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Action of Liraglutide in Patients With Type 2 Diabetes Treated With High-Dose Insulin

Abstract: Treatment with liraglutide significantly improved insulin secretion, even in patients with long-standing T2D requiring high-dose insulin treatment. Liraglutide also decreased liver and sc fat, but it did not alter glucagon secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 52 publications
0
38
0
Order By: Relevance
“…In a recent study, Vanderheiden et al. confirmed the decrease in liver fat and the lack of pancreatic fat decrease in people with T2D requiring high‐dose insulin treatment and treated with liraglutide. This suggests that the effect on liver fat is attributable to a class effect, and that the effect is maintained after long disease duration (a median of 17 years in their study).…”
Section: Discussionmentioning
confidence: 91%
“…In a recent study, Vanderheiden et al. confirmed the decrease in liver fat and the lack of pancreatic fat decrease in people with T2D requiring high‐dose insulin treatment and treated with liraglutide. This suggests that the effect on liver fat is attributable to a class effect, and that the effect is maintained after long disease duration (a median of 17 years in their study).…”
Section: Discussionmentioning
confidence: 91%
“…It is well known that GLP1 agonists reduce visceral fat mass, however, it has still been unknown whether the change in visceral adiposity by GLP1 agonists could be correlated with subsequent changes in albuminuria, hepatic steatosis, and systemic micro-inflammation, all of which are strong contributors to CVD in patients with diabetes [10][11][12]. Vanderheiden A et al have recently reported the efficacy of liraglutide on body composition including visceral adiposity and hepatic fat accumulation in severe obese patients with type 2 diabetes requiring high-dose insulin treatment (>1.5 U/kg/d; average, 2.2 ± 0.9 U/kg/d) [18,19]. They revealed that liraglutide significantly improves hepatic steatosis and reduces subcutaneous fat mass and tends to reduce visceral fat.…”
Section: Discussionmentioning
confidence: 99%
“…Liraglutide is a GLP-1 analogue that stimulates insulin secretion in a glucose-dependent manner [ 12 ]. Liraglutide is indicated for second-line treatment of patients with T2DM in combination with metformin and other oral antidiabetic drugs and/or insulin or as monotherapy if metformin cannot be tolerated or is contraindicated [ 13 ].…”
Section: Introductionmentioning
confidence: 99%